The Effect Of Population Size And Number Of Motor Vehicles On Local Tax Revenue With GRDP As A Moderating Variable - Praja, Rama Bhaskara; Wijaya, Suparna (Educoretax, 2024)
Local taxes play a crucial role in advancing a region. Besides financing local government expenditures, local taxes also enable regional governments to create greater fiscal autonomy, providing flexibility in fund allocation. However, the contribution of local taxes to regional revenue remains relatively small, at only 38%. Therefore, it is essential to identify factors influencing local tax revenues across all provinces in Indonesia to optimize local tax revenue. This research employs linear regression with generalized least square (GLS). The results indicate that the population size, the number of motorized vehicles, Gross Regional Domestic Product (GRDP), interaction between population size and GRDP, and interaction between the number of motor vehicles and GRDP, have a significant effect on local tax revenues simultaneously. However, partially, the population size does not affect local tax revenues. On the other hand, the number of motor vehicles and GRDP positively influence local tax revenues. Furthermore, the moderation regression analysis reveals that GRDP strengthens the influence of the population size on local tax revenues. Conversely, the interaction between GRDP and the number of motor vehicles shows that GRDP weakens the positive effect of the number of motor vehicles on local tax revenues.